General classification of regulations on public administration of labor potential development of higher education institutions - Мороз, С. А. (Аспекти публічного управління, 2015)
The necessity of regulations’ classification was grounded in the article, the content of which is related to the practice of public administration of labor potential development of higher educational institutions. The article contains an analysis and synthesis on catego-rial content of such definitions as «classification» and «legal act». The scientific research organization was based on the existing scientific thought of distribution of regulations for certain classification groups. In the article the author’s approach on the classifica-tion of regulations on public administration of development of labor potential of higher education institutions forms the basic classification groups in the following areas of their grouping: the sphere of influence; the content of the educational system; for object ori-entation; the subjects of management influence; by institutional orientation; the partici-pants of the educational process; the direction of the university; the subjects of law-mak-ing and the level of institutionalization of norms of public administration; the nature of the will of the subjects of public administration; Contextual impact on the system and the structure of the labor potential of universities. In addition, the article the author’s views on building classification scheme grouping regulations and defined communication clas-sification groups according to the level of display management hierarchy administrators.The article concludes the evidence of the variability of proposed classification and openness of its content for further improvement within the development of the regulato-ry mechanism of public administration processes of formation and use of labor potential of higher education institutions. As one of the main results of scientific research, there was submitted justification of public-administrative levels of exposure, and therefore the competence of government relations for the development of labor potential of higher edu-cational establishments.